Early therapeutic effects of an Angiopoietin-1 mimetic peptide in middle-aged rats with vascular dementia - Gao, Huanjia; Findeis, Elizabeth L.; Culmone, Lauren; Powell, Brianna; Landschoot-Ward, Julie; Zacharek, Alex; Wu, Trueman; Lu, Mei; Chopp, Michael; Venkat, Poornima (Frontiers in Aging Neuroscience, 2023)
Background Vascular Dementia (VaD) refers to dementia caused by cerebrovascular disease and/or reduced blood flow to the brain and is the second most common form of dementia after Alzheimer’s disease. We previously found that in middle-aged rats subjected to a multiple microinfarction (MMI) model of VaD, treatment with AV-001, a Tie2 receptor agonist, significantly improves short-term memory, long-term memory, as well as improves preference for social novelty compared to control MMI rats. In this study, we tested the early therapeutic effects of AV-001 on inflammation and glymphatic function in rats subjected to VaD. Methods Male, middle-aged Wistar rats (10–12 m), subjected to MMI, were randomly assigned to MMI and MMI + AV-001 treatment groups. A sham group was included as reference group. MMI was induced by injecting 800 ± 200, 70–100 μm sized, cholesterol crystals into the internal carotid artery. Animals were treated with AV-001 (1 μg/Kg, i.p.) once daily starting at 24 h after MMI. At 14 days after MMI, inflammatory factor expression was evaluated in cerebrospinal fluid (CSF) and brain. Immunostaining was used to evaluate white matter integrity, perivascular space (PVS) and perivascular Aquaporin-4 (AQP4) expression in the brain. An additional set of rats were prepared to test glymphatic function. At 14 days after MMI, 50 μL of 1% Tetramethylrhodamine (3 kD) and FITC conjugated dextran (500 kD) at 1:1 ratio were injected into the CSF. Rats (4–6/group/time point) were sacrificed at 30 min, 3 h, and 6 h from the start of tracer infusion, and brain coronal sections were imaged using a Laser scanning confocal microscope to evaluate tracer intensities in the brain. Result Treatment of MMI with AV-001 significantly improves white matter integrity in the corpus callosum at 14 days after MMI. MMI induces significant dilation of the PVS, reduces AQP4 expression and impairs glymphatic function compared to Sham rats. AV-001 treatment significantly reduces PVS, increases perivascular AQP4 expression and improves glymphatic function compared to MMI rats. MMI significantly increases, while AV-001 significantly decreases the expression of inflammatory factors (tumor necrosis factor-α (TNF-α), chemokine ligand 9) and anti-angiogenic factors (endostatin, plasminogen activator inhibitor-1, P-selectin) in CSF. MMI significantly increases, while AV-001 significantly reduces brain tissue expression of endostatin, thrombin, TNF-α, PAI-1, CXCL9, and interleukin-6 (IL-6). Conclusion AV-001 treatment of MMI significantly reduces PVS dilation and increases perivascular AQP4 expression which may contribute to improved glymphatic function compared to MMI rats. AV-001 treatment significantly reduces inflammatory factor expression in the CSF and brain which may contribute to AV-001 treatment induced improvement in white matter integrity and cognitive function.